Recriando modos de viver : biografema de uma vítima de acidente motociclístico - Santos, Mariana Andrade dos (2014)
This is a research which experience a biographematicapproach, aiming produceabiographeme of a person who suffered a motorcycle accident, this event caused disordes which highly affected his life. How should we tell the story of a life being also sensitive to what happens in our life? The study setting was in the city of Cariacica – ES. The study subject was a Cariacica resident motorcycle passenger whose accident occurred in a trip within the state. The instruments used in the production od material study were interviews, participant observation, field jounal and a esthetic productions. The development of the workfield was in the period of September to December 2013, and consisted of 3 meetings that generat 3 interviews, seven online meeting and the record of observations and affections in the field journal. The meetings happened takin the event (événement) – a concept bay Deleuze and Guattari – as a departing point. Each enconter between the reseacher and the subject was registered in the field journal. The interviews were audio recorded and the esthetic and graphic productions were reprographed. After transcribing the interviews, a sensitive reading of them was performed concomitant to listening to the recordings, seeking in the production of the biographeme to put forth the story we want to tell about those lives, a practice which constitute a sensitive body oarticipant of the research, echoing those lives in ecounter with the city. The biographematic production of the empirical part of the study was developed with inspirations taken from schizoanalysis.